Corrigendum to “Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration” [Carbohydrate Polymers 352 (2025) 123192] - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2026)

MDM2/X mediates reduced apoptosis in the plateau zokor: a mechanism of high-altitude adaptation - Mengchen Zhang; Yi Li; Huiqi Lin; Tianfu Yu; Fangyuan Xia; Mahanand Chatoo; Kexin Li; Honghao Yu; Eviatar Nevo; Jizeng Du; Yang Zhao; Xuequn Chen (Journal of Zhejiang University-SCIENCE B, 2026)

Robust CRISPR/Cas12a genome editing in Brassica vegetables - Guanzhong Huo; Jintai Yu; Wenjing Li; Chao Zhang; Meng Qin; Mingchao Li; Xiaoxiao Yu; Honghao Lv; Jianjun Zhao; Jun Li (Science China Life Sciences, 2026)

Divergent Responses of Cyprinus carpio to Hermetia illucens and Musca domestica Larval Oils: A Matter of Source and Dose in Growth Performance, Lipid Metabolism and Gut Microbiome - Xueliang Sun; Honghao Zhao; Chengxun Chen; Hong Yu; Xiaobo Wang; Hongyue Shi; Weiye Wei; Juan Yang; Zhenzhen Fang (Fishes, 2026)
The search for sustainable alternatives to fish oil (FO) in aquafeeds is imperative for the long-term sustainability of aquaculture. This study evaluated the effects of partially replacing FO with oils derived from Hermetia illucens (RH) and Musca domestica (RY) larvae at 10%, 30%, and 50% levels on growth, lipid metabolism, hepatic antioxidant capacity, and gut microbiota in juvenile Cyprinus carpio. Results showed distinct source- and dose-dependent responses. RY produced a consistent dose-dependent trend in growth parameters, whereas RH exhibited a biphasic pattern, with growth impairment at 30% replacement and recovery at 50%. Both oils significantly suppressed hepatic fatty acid synthase (FAS) activity, yet this suppression was accompanied by dose-dependent up-regulation of fas expression, particularly at high RH and RY levels, indicating complex post-transcriptional regulation. RH at higher replacement levels reduced digestive enzyme activities and antioxidant capacity, while higher RY caused minimal disruption. Both oils reshaped gut microbiota toward oil-specific community structures. Two-way ANOVA revealed significant synergistic interactions between oil source and replacement level for most serum biochemical and hepatic antioxidant parameters (ηp2 > 0.90). These findings demonstrate that RY is a tolerable alternative across a wide replacement range, though all RY groups exhibited lower growth than the control, 30% is identified as the maximum tolerable level; whereas RH requires precise dosing at 10% to avoid the 30% impairment threshold.

Unveiling sulfur-vacancy-induced electron transfer pathways in FeNi2S4 steering peroxydisulfate activation from radical to non-radical oxidation - Yuansheng Wang; Xueming Lin; Zhicong Lan; Jiayi Li; Honghao Zeng; Hanyun Zhang; Min Yu; Jiaqu Tan; Dongya Li; Fan Yang (Chemical Engineering Journal, 2026)

Advances and challenges in CAR-T cell therapy for breast cancer: from molecular design to clinical application - Honghao Yu; Wenzhi Feng; Di Lan; Qianyi Liu; Xia He; Siyu Zhang; Chunyu Tong; Bocui Song (Cancer Causes & Control, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Evolution of Oil Shale Permeability with Depth Under Real-Time High-Temperature Triaxial Stress Conditions - Honghao Yu; Liping Li; Jupeng Tang; Xiao Zhang (Rock Mechanics and Rock Engineering, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Geothermal reservoir reinjection: An experimental and numerical study using a large-scale 3D sand tank - Tao Chen; Tong Bai; Yu Zhang; Yabin Yang; Honghao Sheng; Shuai Liu; Zongjun Gao; Fengxin Kang (Geothermics, 2026)

ARTEMIS: A real-time efficient ortho-mapping and thematic identification system for UAV-based rapid response - Yijun Liu; Akram Akbar; Ting Yu; Yunlong Yu; Yuanhang Kong; Jingwen Gao; Honghao Wang; Yanyi Li; Hongduo Zhao; Chun Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A novel perspective on atrazine-induced stress in potato seedlings and its alleviation by green manure (Vicia villosa): Insights from physiological and underlying mechanisms - Yu Wang; Wansheng Yang; Renyue Ming; Wanqiu Jing; Honghao Cui; Yuping Zhang; Ping Lu (Journal of Hazardous Materials, 2025)

Enabling fast-charging capability of high-voltage solid-state lithium metal batteries by in-situ composite of COF into polymer electrolyte - Jiazhu Guan; Xintian Li; Luqi Zhou; Qinghui Zeng; Yu Liu; Honghao Wang; Yuchen Jiang; Zhenfeng Li; Lin Chen; Yong Cao; Rongzheng Li; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Study of the Bond–slip performance of grouted rockbolt structures under the coupling effects of temperature and corrosion - Shuisheng Yu; Hongsen Zhang; Yuzhou Sun; Yi Zhao; Honghao Yang; Shucan Lu; Fuzhou Qi (Tunnelling and Underground Space Technology, 2025)

Effect of Anion Concentration in the Acidic Environment on Rock’s Mechanical Properties - Haida Yu; Chengguo Zhang; Honghao Chen; Ismet Canbulat; Serkan Saydam (Rock Mechanics and Rock Engineering, 2025)

Frequency veering and coupled vibration of fluid-transporting parallel pipeline systems with constrained layer damping - Hongwei Ma; Wenhao Ji; Yu Zhang; Hui Zhang; Honghao Liu; Wei Sun (Ocean Engineering, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2025)

CO2-responsive preformed particle gels with high strength for CO2 conformance control in heterogeneous reservoirs - Jia-Nan Deng; Honghao Zhao; Hao Zheng; Yuan Zhuang; Kaixuan Wei; Haozhong Yuan; Zhanhua Deng; Yuanxian Gao; Xing Zhou; Tianteng Yu; Huiting Hu; Guiwu Lu; et al. (Fuel, 2025)

Influence of Pyrolysis Degree On Oil Shale Anisotropy and Damage Deterioration Characteristics - Tang Jupeng; Yu Honghao; Zhang Xiao; Zhao Yaru (Rock Mechanics and Rock Engineering, 2025)

Polyimide foams with high porosity in the micrometer range prepared by scrape foaming for thermal insulation - Yu He; Qili Zhou; Wen Wang; Zitan Yang; Zhi Liang; Zhangcheng Li; Honghao Cao; Chong Hou (Chemical Engineering Journal, 2024)

Uncovering chromatin accessibility and cancer diagnostic potential via cell-free DNA utilization - Jie Li; Jiahui Chen; Xin Sun; Heli Yang; Keyong Sun; Chang Liu; Yongwang Wang; Mengyue Xu; Xin Ji; Ji Zhang; Xiaojiang Wu; Anqiang Wang; et al. (Science Bulletin, 2024)

The protective effects of Kefir extract (KE) on intestinal damage in larval zebrafish induced by Oxytetracycline: Insights into intestinal function, morphology, and molecular mechanisms - Yang Qiu; Fujie Yan; Huilin Yu; Honghao Li; Shengyao Xia; Jie Zhang; Jiajin Zhu (Food Research International, 2024)

Rapid ion conduction enabled by synergism of oriented liquid crystals and Electron-Deficient boron atoms in multiblock copolymer electrolyte for advanced Solid-State Lithium-Ion battery - Qinghui Zeng; Yu Liu; Baerlike Wujieti; Zhenfeng Li; Anqi Chen; Jiazhu Guan; Honghao Wang; Yuchen Jiang; Henghui Zhou; Wei Cui; Shi Wang; Liaoyun Zhang (Chemical Engineering Journal, 2024)

An ultralow hysteresis zwitterionic hydrogel crosslinked by functionalized graphene oxide quantum dots for dual-responsive flexible wearable sensors - Yutang Zhou; Honghao Shu; Yuhuan Yao; Xinguo Yang; Chuying Yu; Wenbin Zhong (Chemical Engineering Journal, 2024)

Biochar from phytoremediation plant residues: a review of its characteristics and potential applications - Xueyan Fan; Chunyan Du; Lu Zhou; Yi Fang; Guanhao Zhang; Honghao Zou; Guanlong Yu; Haipeng Wu (Environmental Science and Pollution Research, 2024)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Mucin2 regulated by Ho1/p38/IL-10 axis plays a protective role in polystyrene nanoplastics-mediated intestinal toxicity - Mengxing Cui; Qianmei He; Ziwei Wang; Yongjiang Yu; Huan Gao; Ziqi Liu; Honghao Peng; Han Wang; Xue Zhang; Daochuan Li; Liping Chen; Xiumei Xing; et al. (Environmental Pollution, 2023)

Holocene vegetation dynamics of Horqin Sandy Land in northern China inferred from the phytolith record of a sand-paleosol section - Zhuo Yang; Guizai Gao; Dongmei Jie; Jiangyong Wang; Honghao Niu; Ziping Liu; Meng Meng; Lina Song; Niankang Chen; Yuanxiang Wei; Jihuai Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Novel antiosteoporotic peptides purified from protein hydrolysates of taihe black-boned silky fowl: By larval zebrafish model and molecular docking - Yang Qiu; Jianyue Ying; Fujie Yan; Huilin Yu; Yan Zhao; Honghao Li; Shengyao Xia; Jianchu Chen; Jiajin Zhu (Food Research International, 2023)

Diverse spillover effects of COVID-19 control measures on air quality improvement: evidence from typical Chinese cities - Laijun Zhao; Yu Wang; Honghao Zhang; Ying Qian; Pingle Yang; Lixin Zhou (Environment, Development and Sustainability, 2023)

Effect of E-beam irradiation on the qualitative attributes of shrimp (Penaeus vannamei) - Yan Zhao; Huilin Yu; Honghao Li; Yang Qiu; Shengyao Xia; Jie Zhang; Jiajin Zhu (Food Bioscience, 2023)

Health risk assessment of cadmium exposure by integration of an in silico physiologically based toxicokinetic model and in vitro tests - Yangchun Zhang; Ziqi Liu; Ziwei Wang; Huan Gao; Yuqing Wang; Mengxing Cui; Honghao Peng; Yongmei Xiao; Yuan Jin; Dianke Yu; Wen Chen; Qing Wang (Journal of Hazardous Materials, 2023)

Propagation behavior of hydraulic fractures in shale under triaxial compression considering the influence of sandstone layers - Lei Yang; Xiangchao Sheng; Bo Zhang; Honghao Yu; Xiaolong Wang; Pai Wang; Jie Mei (Gas Science and Engineering, 2023)

Application of transition metal boride nanosheet as sulfur host in high loading Li-S batteries - Zhenfeng Li; Qinghui Zeng; Yang Yu; Yu Liu; Anqi Chen; Jiazhu Guan; Honghao Wang; Wei Liu; Xu Liu; Xiangfeng Liu; Liaoyun Zhang (Chemical Engineering Journal, 2023)

Mulberry leaf extract improves non-specific immunity and antioxidant capacity of largemouth bass (Micropterus salmoides) fed a high-starch diet - Jing Tingsen; Luo Hui; Huang Junwa; Li Zhe; Li Yu; Jin Honghao; Zou Xinxi; Ke Zhenlin; Sun Wenbo; Hou Mengdan; Yang Huijun; Ye Hua (Frontiers in Marine Science, 2022)
A 70-day experiment was conducted to investigate the effects of mulberry leaf extract (MLE) on growth, proximate compositions, antioxidant and plasma biochemical parameters, and indices of non-specific immunity of largemouth bass ( Micropterus salmoides ) fed a high-starch diet. Two hundred eighty largemouth bass (initial body weight, 68.00 ± 0.19 g) were randomly fed seven diets: basal-starch diet (BSD; 8.88% starch), high-starch diet (HSD; 11.42% starch), and HSD diets supplemented with 0.05%, 0.10%, 0.20%, 0.50%, and 1.00% MLE (MLE1, MLE2, MLE3, MLE4, and MLE5, respectively). The results indicated that HSD and MLE did not significantly affect the growth performance of largemouth bass during the experimental period compared with that of the BSD, but the supplementation with more than 0.20% (MLE3, MLE4, and MLE5) MLE significantly decreased the hepatosomatic index (HSI) values, and 1.00% (MLE5) MLE significantly decreased the viscerosomatic index (VSI) values. The whole-body moisture of fish fed an HSD decreased significantly, while the whole-body lipid content increased significantly in the HSD group compared with the BSD group. Compared with HSD, MLE supplementation significantly decreased the moisture and lipid contents in the whole body. Supplementation with more than 0.20% MLE (MLE3, MLE4, and MLE5) significantly decreased the moisture content in the muscle. Supplementation with 1.00% MLE significantly decreased the content of hepatic and muscle glycogen. The malondialdehyde (MDA) content of the HSD group was significantly increased compared to that of the BSD group, whereas more than 0.10% (MLE2, MLE3, MLE4, and MLE5) MLE significantly decreased the MDA content. Additionally, the total antioxidant capacity (T-AOC), catalase (CAT), and glutathione peroxidase (GSH-Px) activities of MLE5 were significantly higher than those of the HSD group. The complement-3 (C3) content and globulin (GLB) in the plasma of the HSD group were significantly lower than those of the BSD group. Plasma C3 levels in the MLE3, MLE4, and MLE5 groups were significantly higher than those in the HSD group. In addition, glucose (GLU) levels in the MLE3, MLE4, and MLE5 groups were significantly lower than those in the HSD group. Supplementation with 0.50% (MLE4) MLE significantly increased the lysozyme (LYZ) content and decreased the activities of alanine transaminase (ALT) and aspartate transaminase (AST). Supplementation with 1.00% MLE significantly increased complement-4 (C4) and GLB contents and alkaline phosphatase (ALP) activity. Overall, these findings suggest that MLE could improve antioxidant capacity, immune function, and glycolipid metabolism, thereby alleviating the negative effects of a high-starch diet in M. salmoides .

A genetic-based population PK/PD modeling of methadone in Chinese opiate dependence patients - Dong Guo; Zhirong Tan; Xiaoya Lou; Shan Shi; Yan Shu; Honghao Zhou; Li Yu; Hong Yang (European Journal of Clinical Pharmacology, 2022)

Kompetitive allele-specific PCR (KASP) genotyping and heterotic group classification of 244 inbred lines in cabbage (Brassica oleracea L. var. capitata) - Zhiyuan Li; Hailong Yu; Xing Li; Bin Zhang; Wenjing Ren; Xiaoping Liu; Zhiyuan Fang; Limei Yang; Mu Zhuang; Honghao Lv; Yangyong Zhang (Euphytica, 2020)

Comparative transcriptome analysis of cabbage (Brassica oleracea var. capitata) infected by Plasmodiophora brassicae reveals drastic defense response at secondary infection stage - Yu Ning; Yong Wang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yumei Liu; Zhansheng Li; Limei Yang (Plant and Soil, 2019)

Identification of a major QTL for seed number per silique in cabbage (Brassica oleracea L. var. capitata) using genotyping by sequencing - Xing Li; Congcong Kong; Hailong Yu; Xiaoping Liu; Zhiyuan Fang; Yumei Liu; Limei Yang; Mu Zhuang; Yong Wang; Honghao Lv; Yangyong Zhang (Euphytica, 2019)

Identification and characterization of resistance for Plasmodiophora brassicae race 4 in cabbage (Brassica oleracea var. capitata) - Yu Ning; Yong Wang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yumei Liu; Zhansheng Li; Limei Yang (Australasian Plant Pathology, 2018)

Association of ABCB1 polymorphisms with prognostic outcomes of anthracycline and cytarabine in Chinese patients with acute myeloid leukemia - Hui He; Jiye Yin; Xi Li; Yu Zhang; Xiaojing Xu; Ming Zhai; Juan Chen; Chenyue Qian; Honghao Zhou; Zhaoqian Liu (European Journal of Clinical Pharmacology, 2015)